Faktor – Faktor yang Berhubungan dengan Kanker Payudara di Poli Onkologi RSU. Bahteramas Provinsi Sulawesi Tenggara 2018 - Zalumin, Zalumin; Tasmin, Tasmin; Torundju, sultan Akbar (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2018)
Breast cancer (Carcinoma mammae) is a malignant neoplasm of parenchyma origin. Every year as many as 12 million people worldwide suffer from cancer and 7.6 million of them die of cancer. Southeast Sulawesi Province is one of the provinces in Indonesia with a high number of breast cancer cases. Southeast Sulawesi Province 128 cases. This study aims to determine the factors associated with the incidence of breast cancer in the Oncology Polyclinic, Bahteramas General Hospital, Southeast Sulawesi. . This type of research is quantitative research with a case control approach design. The case population was all breast cancer patients at Bahteramas General Hospital, Sultra totaling 26 cases from the period May - July 2018. The number for the case sample was 21 people and the control sample was 21 people, the sampling technique used simple random sampling. The analytical test used is the Chi odds ratio. The results of the analysis using the Odds Ratio test obtained conscious behavior (OR = 8,000), Odds Ratio (OR) = 19,200, exposure to information, Odds Ratio (OR) = 10,625 intake of fatty foods, Odds Ratio (OR) = 16,095, Obesity Odds Ratio (OR) = 10,625, stress Odds Ratio (OR) = 16,095. It is hoped that the Bahteramas Hospital, especially the Oncology Polyclinic, will be able to use the results of this study as information and consideration in providing services, especially to breast cancer patients.